Gastroprotective Role of Glucocorticoid Hormones - Ludmila Filaretova; Tatiana Podvigina; Tatiana Bagaeva; Peter Bobryshev; Koji Takeuchi (Elsevier, 2007)
Gastric ulcer disease remains widespread; a stressful lifestyle and nonsteroidal antiinflammatory drugs (NSAIDs) make significant contributions to this pathological situation. The findings overviewed here support the idea that glucocorticoid hormones released in response to acute stress or NSAIDs act as gastroprotective substances and exert many of the same actions in the stomach as prostaglandins (PGs) and nitric oxide (NO) as well as capsaicin-sensitive afferent neurons. Glucocorticoids exert a gastroprotective effect by both maintaining local defensive factors (mucosal blood flow and mucus production) and inhibiting pathogenic elements (gastric motility and microvascular permeability). Furthermore, they exert gastroprotective actions in co-operation with PGs, NO, and the afferent neurons; and their compensatory action is observed when the protective mechanism provided by either of these factors is impaired. The gastroprotective action of glucocorticoids is also associated with maintenance of general body homeostasis, including blood glucose levels and systemic blood pressure. In conclusion, glucocorticoids released in response to acute stress or NSAIDs are naturally occurring protective factors that play an important role in maintenance of the gastric mucosal integrity. This led us to re-evaluate the traditional paradigm that glucocorticoid hormones produced during activation of the hypothalamic-pituitary-adrenocortical axis are ulcerogenic in the stomach. Keywords:: hypothalamic-pituitary-adrenocortical axis, glucocorticoid hormone, stress- and nonsteroidal antiinflammatory drug (NSAID)-induced gastric erosion, gastroprotection